The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3763/asre.2010.0024
|View full text |Cite
|
Sign up to set email alerts
|

Using fractal analysis to compare the characteristic complexity of nature and architecture: re-examining the evidence

Abstract: Over the last few decades Complexity Scientists have shown that many natural systems possess similar geometric patterns that are repeated over multiple scales of observation. Using Euclidean geometry it is impossible to measure these forms as the closer the observer approaches the natural feature with a measuring device, the longer the result becomes. In response to this situation fractal geometry was developed as a means for determining, over progressive scales, the characteristic visual complexity of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
0
23
0
6
Order By: Relevance
“…Keller et al (1987) Further to natural elements, it was found that the fractal geometry can also be useful for quantifying the properties of human creations such as art, architecture and the built environment (Mandelbrot, 1982). Several researchers have used fractal geometry to analyse different aspects of urban environments (Batty & Longley, 1994;Cooper & Oskrochi, 2008;Vaughan and Ostwald, 2010;Perry, 2012). However, Voss (1987) argued that fractal dimension is only appropriate for natural forms with large scales and natural boundaries.…”
Section: Visual Complexity and Fractal Geometrymentioning
confidence: 99%
See 4 more Smart Citations
“…Keller et al (1987) Further to natural elements, it was found that the fractal geometry can also be useful for quantifying the properties of human creations such as art, architecture and the built environment (Mandelbrot, 1982). Several researchers have used fractal geometry to analyse different aspects of urban environments (Batty & Longley, 1994;Cooper & Oskrochi, 2008;Vaughan and Ostwald, 2010;Perry, 2012). However, Voss (1987) argued that fractal dimension is only appropriate for natural forms with large scales and natural boundaries.…”
Section: Visual Complexity and Fractal Geometrymentioning
confidence: 99%
“…Euclidean geometry developed around 300BC is unable to determine the size and complexity of any natural feature in the landscape (Vaughan and Ostwald, 2010). In response to this deficiency, fractal dimension was developed for the determination of complexity of natural systems (Vaughan and Ostwald, 2010).…”
Section: Visual Complexity and Fractal Geometrymentioning
confidence: 99%
See 3 more Smart Citations